Prevalence and determinants of violent disciplinary practices for children in Bangladesh: Evidence from a nationally representative survey - Raisa Rashid Mim; Mohammad Shahed Masud (PLoS ONE, 2025)
Violent discipline, characterized by the use of physical force resulting in bodily pain, discomfort, or resorting to scolding and emotional abuse to correct children’s misbehavior, has gathered considerable attention due to its negative impact on children’s development. This study aims to identify the prevalence and factors associated with different violent disciplinary practices toward children of 1–14 years age in Bangladesh. Utilizing data from the Multiple Indicator Cluster Surveys (MICS) conducted in 2019, this analysis, based on interviews with parents of 70027 children, focuses on three dependent variables measuring violent disciplinary practices: psychological aggression, physical punishment and any violent discipline. The independent variables considered include the child’s age, sex, type of residence (rural or urban), division, education of mothers, child disability, ethnicity and wealth index. Logistic regression models were employed to find the relationships between these variables and different forms of violent discipline, including psychological aggression, physical punishment and any violent discipline (psychological aggression, physical punishment or both), among children in Bangladesh. The results reveal several significant associations with these disciplinary practices. Younger male children, with functional difficulties, those from urban residence and poorer households, residing in the central and southern regions of the country (Khulna, Chattogram), having primary educated mothers and belonging to the Bengali households are at higher risk of any form of violent discipline including psychological aggression, physical punishment. Significantly, our study unveils a strong correlation between any violent discipline and psychological aggression, highlighting that Bangladeshi parents predominantly employ psychological aggression as their primary mode of disciplinary practice. The findings underscore the importance of activating child protection laws and implementing continuous training programs for parents to promote positive parenting practices. To mitigate the use of violent discipline in Bangladesh, the study suggests focusing on improving parental education levels and addressing economic conditions.